Selective detection, quantification, and subcellular location of α-synuclein aggregates with a protein aggregate filtration assay - Michael L. Kramer; Christina Behrens; Walter J. Schulz-Schaeffer (BioTechniques)
Parkinson's disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy are caused by α-synuclein aggregates. At present, there is no good biochemical method defining α-synuclein aggregates formed in vivo versus oligomers as a means to investigate α-synuclein aggregation and its mechanisms of neurodegeneration. A simple method, therefore, for the selective and sensitive detection of α-synuclein aggregates suited for screening purposes would be useful. Since in contrast to prions a proper detection of α-synuclein aggregates by Western blot analysis is difficult, we developed a protein aggregate filtration (PAF) assay. It takes advantage of the inherent insolubility of aggregated α-synuclein using microfiltration to separate it from soluble isoforms. For the first time, this assay even makes quantitative comparisons possible. We describe how the PAF assay can be applied to human brain tissue and animal and cell culture models, as well as used as a screening method for the subcellular location of α-synuclein aggregates. Since it detects the pathological isoform instead of surrogate markers, the PAF assay may have also potential in diagnosis of PD and DLB.